Differences Between the 8th and 9th Editions of the TNM Staging System in Predicting Mortality in Non-Small Cell Lung Cancer Patients Staged with EBUS - Ezgi Demirdöğen; Orkun Eray Terzi; Özge Aydın Güçlü; Ahmet Ursavaş; Mehmet Karadağ (Diagnostics, 2025)
Background: The distinction between N2a and N2b in the lung cancer TNM 9th edition staging system has reduced the heterogeneity of prognosis using the previous staging system. Moreover, this distinction may enable new treatment approaches in non-small-cell lung cancer (NSCLC). We aimed to evaluate the differences in survival between 8th- and 9th-edition staging and the mortality prediction of the TNM 9th edition in NSCLC patients who did not undergo surgical staging and who were “N”-staged with solely endobronchial ultrasound–transbronchial needle aspiration (EBUS–TBNA) without endoscopic ultrasonography (EUS). Methods: Lung cancer patients who were newly diagnosed and staged with EBUS between May 2016 and January 2023 were retrospectively reviewed. Patients were divided into two groups, “All M0 = Model 1” and “T1–2 N1–2–3 M0 = Model 2”, and compared according to their survival for both the 8th and 9th edition TNM staging systems. Cox regression analyses were performed for independent predictors of 2-year mortality. Results: In this retrospective study, a total of 90 patients were included. Most of the patients were male (84.4%), and the mean age of the study group was 64.0 ± 9.6; deceased patients were older (p = 0.024). There were no differences between groups in terms of smoking habit, comorbidities, tumor PET/CT localization, or 8th and 9th N-staging results with EBUS. The median follow-up period was 26 (0–100) months and longer for living patients than deceased patients in both groups (42 (23–100) vs. 18 (0–74), p = 0.03; 36 (24–100) vs. 20 (1–74), p < 0.001). According to the 8th edition of TNM staging, N2 stage (HR 2.26, 95% CI 1.01–5.05, p = 0.045) and N3 disease (HR 3.31, 95% CI 1.43–7.67, p = 0.005) are independent predictors of two-year mortality for Model 1 patients. When patients were staged according to the 9th edition TNM with EBUS, the relationship between N2a and mortality was not significant, while N2B disease increased the 2-year mortality risk by 2.78-fold (95% 1.07–7.22, p = 0.035), and N3 disease increased it by 3.31-fold (95% 1.43–7.67, p = 0.005). Conclusions: According to the TNM 9th edition staging system, we demonstrated that N2b disease significantly increases the risk of mortality in NSCLC cases using systematic mediastinal staging with EBUS–TBNA alone.